Psychological contract, job satisfaction, commitment, and turnover intention: Exploring the moderating role of psychological contract breach in National Collegiate Athletic Association coaches - Bravo, G. A.; Won, D.; Chiu, W. (International Journal of Sports Science & Coaching, 2019)
This study examined the relationship between psychological contract and three work attitudes, job satisfaction, affective commitment, and turnover intention in a sample of National Collegiate Athletic Association coaches. This study also explored the moderating role of the psychological contract by examining coaches' perceptions of the intentional and unintentional breach. A total of 383 coaches responded to the survey that included items in the transactional and relational psychological contract, job satisfaction, affective commitment, and turnover intention. In addition, the sample was split into two groups, intentional breach and unintentional breach based on their responses to a single question regarding the perceived breach status. Results revealed that the transactional contract had a positive influence on job satisfaction and a negative influence on affective commitment. On the other hand, the relational contract had positive influences on both job satisfaction and affective commitment. Job satisfaction had a positive influence on affective commitment, which negatively led to turnover intention, while affective commitment had no significant influence on turnover intention. A multi-group analysis was conducted to test whether the psychological contract breach moderated the paths in the hypothesized model. The paths from transactional contract to satisfaction and commitment as well as from satisfaction to turnover intention were moderated by the psychological contract breach. The transactional contract-job satisfaction relationship was meaningful for the unintentional breach group, while the transactional contract-affective commitment relationship was stronger with the intentional breach group. The job satisfaction-turnover intention relationship was stronger with the intentional breach group than with the unintentional breach group.